2022
DOI: 10.1002/hed.27100
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid nodules of indeterminate cytology in Hispanic/Latinx patients

Abstract: Background: Behavior of differentiated thyroid cancer (DTC) varies among ethnic groups. Recommended management of thyroid nodules with indeterminate cytology (TN-IC) is based on molecular analysis from predominantly non-Hispanic white patients. We hypothesized that TN-IC in Hispanic/Latinx patients would have different features, management, and outcomes and that molecular testing might perform differently in Hispanic/Latinx patients. Methods: Retrospective chart review was performed on 127 TN-IC analyzed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…The results showed (at a 24% cancer prevalence): SN -91% [CI, 79-98], SP -68% [CI, 60-76], NPV -96% [CI, [90][91][92][93][94][95][96][97][98][99], PPV -47% [CI, 36-58] (21) (Table 1). Since the validation study, 14 independent real-world studies have been published and in aggregate show a significant improvement in performance over the Afirma GEC, primarily with improved specificity and a higher benign call rate (BCR) of 65% (as compared to 54% with the Afirma GEC) (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). As expected, some of these studies have also demonstrated that the implementation of Afirma GSC reduced the rate of surgical intervention by 45-68% (40,43).…”
Section: The Role Of Molecular Diagnostics In Itn For Benign Vs Malig...mentioning
confidence: 76%
“…The results showed (at a 24% cancer prevalence): SN -91% [CI, 79-98], SP -68% [CI, 60-76], NPV -96% [CI, [90][91][92][93][94][95][96][97][98][99], PPV -47% [CI, 36-58] (21) (Table 1). Since the validation study, 14 independent real-world studies have been published and in aggregate show a significant improvement in performance over the Afirma GEC, primarily with improved specificity and a higher benign call rate (BCR) of 65% (as compared to 54% with the Afirma GEC) (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). As expected, some of these studies have also demonstrated that the implementation of Afirma GSC reduced the rate of surgical intervention by 45-68% (40,43).…”
Section: The Role Of Molecular Diagnostics In Itn For Benign Vs Malig...mentioning
confidence: 76%